2011
DOI: 10.1007/s12032-011-0123-6
|View full text |Cite
|
Sign up to set email alerts
|

High expression of tumor-infiltrating macrophages correlates with poor prognosis in patients with diffuse large B-cell lymphoma

Abstract: Diffuse large B-cell lymphoma (DLBCL) is characterized by its clinical and biological heterogeneity. Although the International Prognostic Index (IPI) provides a clinical model for risk stratification of patients with DLBCL, notable variability in outcome is still observed within the same IPI category. Tumor-infiltrating macrophages (also called Tumor-associated macrophages) are the major component in the microenvironment of DLBCL. Their correlation with the prognosis of DLBCL remains controversial. Using a CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 22 publications
1
76
0
1
Order By: Relevance
“…Whereas Nam et al 8 reported similar findings, as mentioned above, and the study by Cai et al 15 also showed that CD68 is a marker of poor outcome in CHOP-treated DLBCL patients, the studies by Hasselblom et al, 16 Meyer et al 17 and Coutinho et al 18 did not reveal significant associations between CD68 protein expression and survival. Furthermore, Wada et al 19 and Marchesi et al 20 reported that an M2 macrophage phenotype, as defined by double staining for CD68 and CD163, is associated with adverse outcome in R-CHOP-treated patients, whereas an M1 phenotype is not.…”
mentioning
confidence: 54%
“…Whereas Nam et al 8 reported similar findings, as mentioned above, and the study by Cai et al 15 also showed that CD68 is a marker of poor outcome in CHOP-treated DLBCL patients, the studies by Hasselblom et al, 16 Meyer et al 17 and Coutinho et al 18 did not reveal significant associations between CD68 protein expression and survival. Furthermore, Wada et al 19 and Marchesi et al 20 reported that an M2 macrophage phenotype, as defined by double staining for CD68 and CD163, is associated with adverse outcome in R-CHOP-treated patients, whereas an M1 phenotype is not.…”
mentioning
confidence: 54%
“…1 An increase in the number of TAM has been associated with shortened survival and drug-resistance in patients with hematologic malignancies such as classic Hodgkin's lymphoma, follicular lymphoma, diffuse large B-cell lymphoma, and multiple myeloma. [2][3][4][5] Macrophages are also involved in the ingestion of rituximab-opsonized cells via the Fcγ receptor and may have a role in rituximab resistance. 6 TAM derive from monocytic precursors circulating in the blood and are recruited into the tumor tissues by chemoattractants.…”
Section: Introductionmentioning
confidence: 99%
“…The monocytic population in chronic lymphocytic leukemia shows altered composition and deregulation of genes involved in phagocytosis and inflammation Rossana Maffei, 1 Jenny Bulgarelli, 1 Stefania Fiorcari, 1 Linda Bertoncelli, 2 Silvia Martinelli, 1 Carla Guarnotta, 3 Ilaria Castelli, 1 Silvia Deaglio, 4 Giulia Debbia, 1 Sara De Biasi, 2 Goretta Bonacorsi, 1 Patrizia Zucchini, 1 Franco Narni,…”
mentioning
confidence: 99%
“…Recent studies demonstrated the important function of TAMs in the progression of cancers 15, 16, 17, 30. Hans et al.…”
Section: Survival‐related Genes Were Selected For Testingmentioning
confidence: 99%